Pelatihan Penggunaan Publish or Perish bagi Guru di SMK Negeri 1 Somambawa - Zulfah; Astuti (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2024)
Improving the quality of education does not only depend on teaching skills, but also on teachers' ability to conduct research and produce scientific works. One of the obstacles often faced by teachers is the lack of knowledge and skills in accessing and analyzing relevant scientific references to support their professional development. This study aims to provide training in the use of the Publish or Perish application to teachers at SMK Negeri 1 Somambawa in order to improve their ability to search for, analyze, and utilize scientific references. This activity is motivated by the need for teachers to improve their academic competence, especially in conducting research and scientific publications. The method used is direct training which includes material presentation, application usage practice, and group discussions. The results of the training showed that teachers were able to understand the functions of Publish or Perish, such as searching for scientific articles, citation analysis, and managing references effectively. The evaluation showed an increase in participants' understanding of how to search for relevant and reliable literature. Thus, this training makes a real contribution to supporting the development of teacher professionalism in the field of research and scientific publication.